Réponses

  • Utilisateur Brainly
2014-05-15T19:21:21+02:00
70 : 5x-4y = -2 x+2y = 4 en multipliant x+2y=4 par -5, on vas enlever x : 5x+4y = -2 -5(x+2y) = 4 5x+4y = -2 -5x-10y = -20 -6y = -22 y = 22/6 = 11/3 5x+4y = -2 5x+(44/3) = -2 15x = -44-6 15x = -50 x = -50/15 = -10/3 verif : x+2y = 4 -10/3 + 22/3 = 12/3 5x+4y = -2 -5x-10y = -20
2x+3y = 1
3x+4y = 2

-3(2x+3y) = 1
+2(3x+4y) = 2

-6x-9y = -3
+6x+8y = 4

-y = 1
y = -1

2x+3y = 1
2x-3 =1
2x = 4
x = 2
probleme :
x+y = 3000
45x+60y = 162000

par substitution :
x =-y+3000

45(-y+3000)+60y = 162000
-45y+135000+60y = 162000
15y = 162000-135000
y = 1800

x+y = 3000
x+1800 = 3000
x = 1200
Merci :)